Factors Influencing the Hydration, Dimensional Stability, and Strength Development of the OPC-CSA-Anhydrite Ternary System - Zhenzhen Yang (MDPI AG, 2021)
Due to the advantages of high early strength and rapid setting, ternary systems consisting of ordinary Portland clinker (OPC), calcium sulphoaluminate (CSA) clinker, and anhydrite have broad application prospects. However, further studies need to be undertaken to find a more optimal mixing proportion of this ternary binder in order to meet basic performance requirements. In this paper, isothermal calorimetric tests, chemical shrinkage tests, drying shrinkage tests, and compressive strength tests were carried out to systematically identify the effect of the OPC/CSA ratio and anhydrite dosage on the hydration, mechanical property development, and dimensional stability of ternary binders. It was found that a higher CSA content leads to a higher cumulative hydration heat, a shorter acceleration period, and a delayed induction period, which can be ascribed to the retardation of C3S at a high aluminate concentration. However, a higher addition of anhydrite can retard the main peak of hydration despite promoting the intermediate peak and improving the hydration reaction rate. The drying shrinkage of blends decreases first along with the CSA proportion and then increases. Moreover, a higher anhydrite content mitigates the drying shrinkage and hinders the strength development. Finally, considering the properties of both the fresh and hardened binder, the ternary blends with 5% anhydrite and OPC/CSA ratios ranging from 3/7 to 2/8 were identified as most suitable for applications that require a high early strength, stable late strength, and small level of shrinkage.